MEMBEDAH MITOS KAPUHUNAN DI KALIMANTAN DARI ASPEK PSIKOLOGI - Putri, Ajeng Anggoro (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2019)
In Indonesia, there are many myths from various regions. In Kalimantan, there is a myth that called kapuhunan. Kapuhunan is bad luck or disaster that occurs when we reject the food offered or do not have time to eat the food that has been served. Myth gives people something to be trusted and feared; myth also bring hope to humans. If there?s no myth, there?s no value to regulate the activities of human life. The negative perceptions of the kapuhunan made the local people anxious if they did not have time to eat the food that had been served. One process of the occurrence of anxiety is the perception of situation. It is important to know about the process of forming perceptions and anxiety can change negative perceptions into positive perceptions. The myth that we believe can form perceptions and anxiety.